Myo-inositol effect on pregnancy outcomes in infertile women undergoing in vitro fertilization/intracytoplasmic sperm injection: A double-blind RCT - Fariba Seyedoshohadaei; Shahin Abbasi; Masoumeh Rezaie; Azra Allahvaisi; Mohammad Jafar Rezaie; Nasrin Soufizadeh; Khaled Rahmani (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Myo-inositol is an intracellular mediator which is involved in various aspects of reproduction in women. Objective: This study aimed to evaluate the impact of Myo-inositol on the outcomes of in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles in infertile women. Materials and Methods: This double-blind randomized controlled trial was conducted on 70 infertile women referred to the Infertility Treatment Center, Besat hospital, Sanandaj, Iran from May 2019 to September 2019 for IVF/ICSI cycles. The participants were randomly divided into 2 intervention (n = 36) and control (n = 34) groups. The intervention group received 2000 mg of Myo-inositol and 200 mcg folic acid twice a day for 2 months and the control group received 200 mcg of folic acid twice a day for 2 months in the IVF/ICSI cycles (from the third day of cycle until the end of the second month). Finally, the number of oocytes, the quality of embryos, and the IVF/ICSI outcomes were compared between the 2 groups. Results: The mean numbers of oocytes, MII oocytes, and 2 pronuclear embryos were significantly higher in the intervention group than the control group. Also, the clinical pregnancy and live birth rates in the intervention group were significantly higher than in the controls (p = 0.04). Conclusion: The administration of Myo-inositol may increase clinical pregnancy and live birth rates by increasing the number of total and meiosis II oocytes in infertile women undergoing IVF/ICSI.